The determinants of financial industry profitability in Malaysia / Nurul Syuhada Baharuddin and Siti Nurul Ashykin Azmi - Baharuddin, Nurul Syuhada; Azmi, Siti Nurul Ashykin (Universiti Teknologi MARA, Terengganu, 2015)
Profitability is one of the important roles that gauge the growth of financial organization. Using a data set period 2001 to 2011, this paper evaluates the impacts of internal and external determinants conditions towards the profitability of financial institution by using static panel data analysis that consist of 21 organization that listed in Bursa Malaysia. The specific determinants of profitability include equity management, asset management, size of organization and inflation. This study employs regression model in order to investigate the relation of explanatory variables towards profitability. This study supports strong recommendations that internal factors should be taken into account when determining profitability of a firm but external factor should have more evaluation and analysis because there is positive insignificant result appear. This study suggests that equity management is the most eligible factor that the variation of profitability. The highest of equity management, the risk in obtain the profitability will reduced as the larger financial services.